ANALISIS HUBUNGAN PENGENDALIAN INTERNAL VERSI COSO TERHADAP INDIKASI KECURANGAN LAPORAN KEUANGAN PADA BAITUL QIRADH ANGGOTA PUSAT KOPERASI SYARIAH NANGGROE ACEH DARUSSALAM - Auliana Yuwannita; Nita Erika Ariani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
Indications of fraud financial statements do not only occur in the public sector or in the banking sector, but can also occur in a cooperative sharia as Baitul Qiradh. Where indications of fraud financial statements occurred due to a weak internal controls in an agency. Internal control framework that identifies the factors that cause the occurrence of fraud established by the Committee of Sponsoring Organizations of Treadway Commission (COSO).This study aims to determine the relationship between the version of the COSO internal control of the financial statements toward indications of fraud (fraud) at Baitul Member Qiradh Sharia Cooperative Center (Puskopsyah) Nanggroe Aceh Darussalam. This study is a primary research using quantitative methods, by using a questionnaire as a research instrument. Questionnaires that successfully analyzed were 66 questionnaires. The data obtained from the questionnaires then processed using SPSS 21 software.This research included the census where data obtained from each employee's overall in Baitul Qiradh which are members of Puskopsyah. Because the population of this study is Baitul Qiradh member Puskopsyah NAD. Spearman Rank method used as a method of analysis to determine the relationship of the variables involved. The results showed that there is a significant relationship between the variables version of COSO internal control for indications of fraud financial statements with a value of coefficient of 0.609. Keywords—: internal control, COSO, Indicative Financial Statement Fraud, Cooperative Sharia, Baitul Qiradh.